Global Recession and Diamond Industry Workers: A Socio Economic Perspective - Sen, Vinod; Solanki, Mukesh Kumar; Kisan, Jadhav Kishor (Economic Literature, 2016)
The recent globalization recession (2007-08) and its effect is all pervasive, the only 1 2 3 difference is of magnitude. Gems and Jewelry is of the largest contributor in India’s total export. Out of this total export of India diamond contributes more than 12 per cent. Gujarat is the one of the biggest player in diamond processing (cutting and polishing) and contributes about 72 per cent of the total exports of India. As diamond industry is mainly export based industry, during recession it adversely gets affected. This paper is an attempt to evaluate the effect of the global slowdown on the cutting and polishing worker. The paper is a case study of diamond industry workers of Surat based on the primary and secondary data that has been collected from 100 diamond cutting and polishing workers of the diamond industry located in Surat of Gujarat. The paper comes up with the conclusion that the recent recession adversely affected the socio-economic condition of the diamond worker and the scheme of social and economic benefits to the effected people fails miserably to support. Economic Literature, Vol. XI (47-53), June 2013